Expression of Pumpkin CmbHLH87 Gene Improves Powdery Mildew Resistance in Tobacco - Guo, Wei-Li; Chen, Bi-Hua; Guo, Yan-Yan; Chen, Xue-Jin; Li, Qing-Fei; Yang, He-Lian; Li, Xin-Zheng; Zhou, Jun-Guo; Wang, Guang-Yin (Frontiers in Plant Science, 2020)
Powdery mildew (PM), caused by Podosphaera xanthii, is a major threat to the global cucurbit yield. The molecular mechanisms underlying the PM resistance of pumpkin (Cucurbita moschata Duch.) are largely unknown. A homolog of the basic helix-loop-helix (bHLH) transcription factor was previously identified through a transcriptomic analysis of a PM-resistant pumpkin. In this study, this bHLH homolog in pumpkin has been functionally characterized. CmbHLH87 is present in the nucleus. CmbHLH87 expression in the PM-resistant material was considerably downregulated by PM; and abscisic acid, methyl jasmonate, ethephon, and NaCl treatments induced CmbHLH87 expression. Ectopic expression of CmbHLH87 in tobacco plants alleviated the PM symptoms on the leaves, accelerated cell necrosis, and enhanced H2O2 accumulation. The expression levels of PR1a, PR5, and NPR1 were higher in the PM-infected transgenic plants than in PM-infected wild-type plants. Additionally, the chlorosis and yellowing of plant materials were less extensive and the concentration of bacteria at infection sites was lower in the transgenic tobacco plants than in the wild-type plants in response to bacterial wilt and scab pathogens. CmbHLH87 may be useful for genetic engineering of novel pumpkin cultivars in the future.